COMPLEMENTARITY OF PECULIAR VELOCITY SURVEYS AND REDSHIFT SPACE DISTORTIONS FOR TESTING GRAVITY - Kim, Alex G.; Linder, Eric V. (PHYSICAL REVIEW D, 2020)
Peculiar-velocity surveys of the low-redshift universe have significant leverage to constrain the growth rate of cosmic structure and test gravity. Wide-field imaging surveys combined with multiobject spectrographs [e.g., ZTF2, Large Synoptic Survey Telescope (LSST), DESI, and 4MOST] can use type Ia supernovae as informative tracers of the velocity field, reaching few percent constraints on the growth rate fσ8 at z ≲ 0.2 where density tracers cannot do better than ∼10%. Combining the high-redshift DESI survey mapping redshift space distortions with a low-redshift supernova peculiar velocity survey using LSST and DESI can determine the gravitational growth index to σðγÞ ≈ 0.02, testing general relativity. We study the characteristics needed for the peculiar velocity survey, and how its complementarity with clustering surveys improves when going from a ΛCDM model assumption to a w0–wa cosmology
Keywords: Type of access: Open Access; Cosmology; gravity